An Update on Molecular Pathways Regulating Vasculogenic Mimicry in Human Osteosarcoma and Their Role in Canine Oncology - Massimini, Marcella; Romanucci, Mariarita; De Maria, Raffaella; Della Salda, Leonardo (Frontiers in Veterinary Science, 2021)
Canine tumors are valuable comparative models for the human counterparts, especially to explore novel biomarkers and to understand pathways and processes involved in metastasis. Vasculogenic mimicry (VM) is a unique property of malignant cancer cells, which promote metastasis. Thus, it represents an opportunity to investigate both the molecular mechanisms and the therapeutic targets of a crucial phenotypic malignant switch. Even though this biological process has been largely investigated in different human cancer types, including osteosarcoma, it is still largely unknown in veterinary pathology, where it has been mainly explored in canine mammary tumors. The presence of VM in human osteosarcoma is associated with poor clinical outcome, reduced patient survival and increased risk of metastasis and it shares the main pathways involved in other type of human tumours. This review illustrates the main findings concerning VM process in human osteosarcoma, searching for the related current knowledge in canine pathology and oncology and the potential involvement of multiple pathways in VM formation, in order to provide a basis for future investigations on VM in canine tumors.